2022
DOI: 10.1007/s41471-021-00128-2
|View full text |Cite
|
Sign up to set email alerts
|

Information Asymmetries and Intra-Company Monitoring: an Empirical Analysis of Nonlinear Relationships Between Company Characteristics and the Size of the Internal Audit Function

Abstract: The internal audit function (IAF) has become one of the main pillars of good corporate governance. Empirical findings show that the size of the IAF varies considerably across companies. This study analyzes the relationships between selected company characteristics as determinants of intra-company information asymmetries and the size of the IAF as an indicator of intra-company monitoring. We test these relationships by analyzing comprehensive survey data obtained from chief audit executives from 283 Austrian, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This may be explained according to agency theory (Jensen and Meckling, 1976). The information exchange between agents (auditor) and principals (senior management) is asymmetric (Eulerich and Lohmann, 2022), influencing access to information (Adams, 1994; Lopes et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained according to agency theory (Jensen and Meckling, 1976). The information exchange between agents (auditor) and principals (senior management) is asymmetric (Eulerich and Lohmann, 2022), influencing access to information (Adams, 1994; Lopes et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained according to agency theory (Jensen and Meckling, 1976). The information exchange between agents (auditor) and principals (senior management) is asymmetric (Eulerich and Lohmann, 2022), influencing access to information (Adams, 1994;Lopes et al, 2023). The agency theory generally assumes that principals (senior managements) may not trust their agents (auditors) due to opportunistic behaviours (Singh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…showed that the investigation of culturally different markets might enhance the understanding of various IA facets. Eulerich and Lohmann (2022) Discussed the reasons for the inconsistency of information and control by investigating the relationship between the characteristics of the company and the size of the IAFs. Using a sample from three countries, Germany, Austria, and Switzerland, the results revealed that there are common characteristics that affect information and control inconsistency, as well as their impact on the size of IAFs.…”
Section: Geographical Distribution Of the Literaturementioning
confidence: 99%
“…It is clear from Table 5, that the questionnaire is the most applied tool that was used in 65 (45.77%) studies. This approach has been used in several studies (i.e., Ježovita et al, 2018;Koutoupis et al, 2018;Alzeban and Sawan, 2015;Eulerich and Lohmann, 2022) as it helps to collect more information that cannot be measured by the secondary data. This is an indication that the results of the studies are realistic to some extent, considering that the use of the questionnaire in administrative and social disciplines is one of the most important ways to obtain reliable and real data (Roopa and Rani, 2012).…”
Section: Research Instrumentsmentioning
confidence: 99%
“…The starting point for a value-adding IAF is commonly offered by the three lines model (Bantleon et al, 2021;Eulerich, 2021) pointing out that internal auditing supports governance actors along with monitoring and oversight activities through independent and objective assurance and advice. Thus, internal auditing has gained considerable acceptance as a crucial element of good corporate governance (Carcello et al, 2020;Eulerich & Lohmann, 2022).…”
Section: Involvement Of Internal Auditorsmentioning
confidence: 99%